Cephalopod proteins for bioinspired and sustainable biomaterials design - Iana Lychko; Inês Padrão; Afonso Vicente Eva; Catarina Alexandra Oliveira Domingos; Henrique Miguel Aljustrel da Costa; Ana Margarida Gonçalves Carvalho Dias; Ana Cecília Afonso Roque (Materials Today Bio)
Nature offers a boundless source of inspiration for designing bio-inspired technologies and advanced materials. Cephalopods, including octopuses, squids, and cuttlefish, exhibit remarkable biological adaptations, such as dynamic camouflage for predator evasion and communication, as well as robust prey-capturing tools, including beaks and sucker-ring teeth that operate under extreme mechanical stresses in aqueous environments. Central to these remarkable traits are structural proteins that serve as versatile polymeric materials. From a materials science perspective, proteins present unique opportunities due to their genetically encoded sequences, enabling access to a diversity of sequences and precise control over polymer composition and properties. This intrinsic programmability allows scalable, environmentally sustainable production through recombinant biotechnology, in contrast to petroleum-derived polymers. This review highlights recent advances in understanding cephalopod-specific proteins, emphasizing their potential for creating next-generation bioengineered materials and driving sustainable innovation in biomaterials science.